Michel Foucault historian of the present - HADDOUCHE, Zahir (Journal of Human Sciences, 2019)
The Foucauldian undertaking endeavors to trace a critical-historical diagnosis of Western culture in order to write the history of the present because the question of the present is placed at the focus of philosophical reflection, and the task of philosophy, according to Foucault, does not consist to seek the formal conditions of truth or to determine the supra-historical essence, but to make the diagnosis of the present.